SISTEM PAKAR MENDETEKSI GANGGUAN JIWA SKIZOFRENIA BERBASIS ANDROID EXPERT SYSTEM DETECT A MENTAL DISORDER SCHIZOPHERNIA BASED ON ANDROID (Information Technology and Telematics, 2015)
Abstract – Usual problems of mental disorders often occur in almost all countries in the world. Statistics presented by the WHO's research center in 1990 states that, each time for 1% of the population in the world having psychiatric disorders and in a state of need and treatment. Schizophrenia is a psychiatric disorder that affects the mental disorders, and these disorders characterized by disturbances in thought processes and emotional weak. Based on the description above background bermakasud author makes an application to detect mental disorder schizophrenia in order to facilitate the layman to detect psychiatric disorders, so much faster in detecting psychiatric disorders Schizophrenia. This application can be used anywhere and anytime because it can be run through mobile android smartphone and light on the run since the application is offline (without internet connection). Keywords: Android, Smartphone, Service center, Skizofrenia.